Electrophysiological assessment of aphakic cystoid macular oedema. Issue 11 (November 1986) - Salzman, J; Seiple, W; Carr, R; Yannuzzi, L
Abstract : Focal electroretinograms (FERG), pattern electroretinograms (PERG), and visual evoked potentials (VEP) were studied in a group of 30 aphakic patients with cystoid macular oedema (ACME). When compared with a control group of age-matched aphakics, 35% of patients were found to have abnormal FERG responses and 53%–over half of whom had normal FERG responses–showed abnormal PERG amplitudes. Although most of the patients had associated optic disc leakage, VEP latencies were normal in 26 out of 30. These results may explain the more severe visual loss seen in some ACME patients where the ophthalmologically visible retinal changes do not seem sufficient to explain such reduction in vision.